Principles of GLP - Long, David (Henry Stewart Talks, 2012)
Where does GLP fit into the R&D model?, FDA vision of R&D, Successive R&D phases, Regulation, Good "X" practices, Pharmaceutical R&D model, R&D spending and success, Compliance to GLP, Economic, ethical, scientific and regulatory reasons, GLP: a quality management system (QMS), GLP as a quality assurance system, Planning of scientific studies, Study performance, Raw data acquisition, Study report, Archive, Monitoring, The basics of GLP: a different perspective, Documentation, Traceability/reconstruction